Public procurement accounting as a tool to end corruption in Ghana: Forensic Accounting Perspective - Emmanuel, Ampong Afoakwah; Doris, Amoako; Hannah, Kemevor (Journal of Social Sciences and Management Studies, 2023)
This study's goal was to show how, by applying natural principles to human laws, forensic accounting might be utilized as a tactic to combat corruption in public procurement. Ten public universities in Ghana were selected for the survey, and in 2023 it examined views regarding policy fairness, government performance, and deterrent. 109 questionnaires were distributed to the procurement officers of the selected institutions using a simple random sampling. The collected data were subjected to a multiple linear regression analysis using the Smart PLS software. The study concluded that forensic accounting was ineffective in stopping procurement misconduct. It also discovered that there is currently very little usage of forensic accounting by the government. Governments at all levels ought to be more interested in forensic accounting and accountants, the report suggests, in order to keep an eye on and look into fraud cases that have been shown to be fraudulent. The management of the procurement authority needs to improve the criminology training provided to accountants and auditors. This training should concentrate on topics such as the nature and extent of financial crimes, ethical concerns, investigation, and remediation. This is necessary if forensic science is to be utilized as the primary tool for corruption and fraud prevention. The administration must also give careful consideration to the impartiality, independence, and reason of the courts.